A comparative study of antenatal and fetal complications in pregnant women with and without history of polycystic ovary syndrome - Meghwal, Suman; Rajoriya, Lata; Shankar, Ambika; Malik, Rupal; Dhaka, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Polycystic ovary syndrome in the present generation is a very common reproductive disorder and the prevalence is on the rise. Aim of the current study was to compare the maternal outcome in normal and women with PCOS. Methods: This study was a case-control study conducted in Department of Obstetrics and Gynaecology, SMS Medical College and attached group of hospitals, Jaipur from May 2019 to August 2020. Pregnant women with history of PCOS were taken as cases and with no such history were controls. Results: 9.49% women developed gestational diabetes mellitus (GDM) in cases as compared to 1.61% women in control group. The difference in the incidence of GDM in the two groups was statistically significant. When hypertensive disorders of pregnancy were considered, a statistically significant difference was observed as 11.2% cases and 2.42% controls showed HDP. Mean birth weight of neonate in cases was 2.43±0.31 kg and in control group was 2.71±0.29 kg. Mean APGAR score at 1 minute in cases was 6.21±1.23 and in controls was 7.21±0.24. APGAR score at 5 minutes in PCOS group was 7.89±1.40 and in control group was 8.12±0.21. 12 neonates from the cases group were admitted in NICU. The difference was statistically significant when compared Conclusions: With a detailed comparative analysis of this case-control study, it can be concluded that many antenatal and fetal complications are per se increased in women with a history of PCOS.